P353 The Current Status Of Evidence-Based Clinical Practice Guidelines On Stroke. (15th August 2013) - Jang, B; Park, S; Park, J; Cheon, C; Go, H; Sun, S; Ko, S
Abstract : Background: Stroke is one of the main causes of death. It is important not only treating acute state after stroke event, but managing patients with disability. Objectives: To examine current status of evidence-based CPGs for stroke. Methods: We were systematically examined CPGs of stroke since 2000. We searched Korean DB and PubMed, NGC, GIN using 'stroke'. Data were extracted on types of treatment, management and rehabilitation, and level of evidence (LOE), grade of recommendation (GOR), and the included CPGs was evaluated though AGREE II. Results: Finally 24 CPGs were selected, and 20 were since 2006. 9 CPGs were from academic societies or agencies in USA, 7 from Europe, and 8 from others. The number of CPGs wrote by academic institutes 24, and 14 published in the medical journals. On both hemorrhage and infarction were 15, on infarction 5, and on hemorrhage 4. Major issues of 6 CPGs were from treatment and management of acute stage to rehabilitation of chronic stage, 10 were only treatment and management of acute phase, and 8 were about stroke rehabilitation. All CPGs didn't present the LOE and GOR. It is various that criteria for LOE and GOR. Discussion: Although all CPGs were 'evidence-based', there was not equal. When developing new CPGs from other regions, it is necessary to consider taking into account the diversity of these. Implications for Guideline Developers: Recently there are many cases of 'adaptation' from existing CPGs, but it could be seen the diversity of contents and level of CPGs in this study.